(untitled) (Baghdad Science Journal, 2021)
In this work, the effect of atomic ratio on structural and optical properties of SnO2/In2O3 thin films prepared by pulsed laser deposition technique under vacuum and annealed at 573K in air has been studied. Atomic ratios from 0 to 100% have been used. X-ray diffraction analysis has been utilized to study the effect of atomic ratios on the phase change using XRD analyzer and the crystalline size and the lattice strain using Williamson-Hall relationship. It has been found that the ratio of 50% has the lowest crystallite size, which corresponds to the highest strain in the lattice. The energy gap has increased as the atomic ratio of indium oxide increased.